A randomized, double-blind, placebo-controlled study of omalizumab combined with oral immunotherapy for the treatment of cow's milk allergy - Wood, Robert A.; Kim, Jennifer S.; Lindblad, Robert; Nadeau, Kari; Henning, Alice K.; Dawson, Peter; Plaut, Marshall; Sampson, Hugh A. (Journal of allergy and clinical immunology, 2016)
Although studies of oral immunotherapy (OIT) for food allergy have shown promise, treatment is frequently complicated by adverse reactions and, even when successful, has limited long-term efficacy because benefits usually diminish when treatment is discontinued. We sought to examine whether the addition of omalizumab to milk OIT reduces treatment-related reactions, improves outcomes, or both. This was a double-blind, placebo-controlled trial with subjects randomized to omalizumab or placebo. Open-label milk OIT was initiated after 4 months of omalizumab/placebo with escalation to maintenance over 22 to 40 weeks, followed by daily maintenance dosing through month 28. At month 28, omalizumab was discontinued, and subjects passing an oral food challenge (OFC) continued OIT for 8 weeks, after which OIT was discontinued with rechallenge at month 32 to assess sustained unresponsiveness (SU). Fifty-seven subjects (7-32 years) were randomized, with no significant baseline differences in age, milk-specific IgE levels, skin test results, or OFC results. At month 28, 24 (88.9%) omalizumab-treated subjects and 20 (71.4%) placebo-treated subjects passed the 10-g “desensitization” OFC (P = .18). At month 32, SU was demonstrated in 48.1% in the omalizumab group and 35.7% in the placebo group (P = .42). Adverse reactions were markedly reduced during OIT escalation in omalizumab-treated subjects for percentages of doses per subject provoking symptoms (2.1% vs 16.1%, P = .0005), dose-related reactions requiring treatment (0.0% vs 3.8%, P = .0008), and doses required to achieve maintenance (198 vs 225, P = .008). In this first randomized, double-blind, placebo-controlled trial of omalizumab in combination with food OIT, we found significant improvements in measurements of safety but not in outcomes of efficacy (desensitization and SU).